PEMANFAATAN PLASTIK DARI REJEK INDUSTRI KERTAS UNTUK BAHAN BAKAR (Utilization of Plastics Reject of Paper Industry for Fuel) - Yusup Setiawan; Sri Purwati; Aep Surachman; Reza Bastari I. W.; Kristaufan Joko Pramono (Center for Pulp and Paper, 2016)
Utilization of reject plastic pellet of paper mill which is waste paper as the raw material has been carried out. Making of reject plastic pellet was consisted of wet shredded process of reject using shredded machine, separation process of plastic and fiber with filtration process, and drying process of wet shredded plastic using centrifugal drainer machine and sun-drying. Dried shredded reject plastic was then formed plastic pellet using pellet machine. Plastic pellets produced has diameter of around 10 mm and a length of about 10-15 mm. Plastic pellets were analyzed for proximate analysis (moisture, ash, volatile matter and fixed carbon contents). In addition, it was also tested for calorific value, sulfur content, ash mineral content and the ash fusion temperature (AFT). The results indicate that the reject plastic pellets have a high calorific value (7,207-8,730 cal/g), low sulfur content (0.14 to 0.17%), low ash mineral content, and the Ash Fusion Temperature (AFT) above the operating temperature of the boiler (900oC). Reject plastic pellets in the amount of 4.25% of production capacity could potentially be used as a coal substitution for fuel boiler of paper mill with a low propensity of slagging and fouling in the boiler.Keywords: coal, paper mill, pellets, plastic, reject, fuel ABSTRAKPenelitian pemanfaatan pelet plastik rejek industri kertas berbahan baku kertas bekas telah dilakukan. Pembuatan pelet plastik dari rejek meliputi tahapan proses pencacahan rejek secara basah menggunakan mesin pencacah, proses pemisahan cacahan plastik dan serat dengan proses penyaringan, dan proses pengeringan cacahan plastik rejek basah menggunakan mesin peniris sentrifugal dan panas sinar matahari. Cacahan plastik rejek kering selanjutnya dibentuk pelet plastik menggunakan mesin pelet. Pelet plastik yang dihasilkan berdiameter 10 mm dengan panjang sekitar 10 – 15 mm. Pelet plastik dari rejek dianalisis proksimat (kadar air, kadar abu, kadar zat terbang dan kadar karbon padat). Selain itu, pelet dianalisis juga nilai kalor, kadar sulfur, kadar mineral abu dan Ash Fusion Temperature (AFT). Hasil menunjukkan bahwa pelet plastik dari rejek memiliki nilai kalor tinggi (7.207 – 8.730 kal/g), kadar sulfur rendah (0,14 – 0,17%), kadar mineral abu rendah, dan Ash Fusion Temperature(AFT) di atas suhu operasi boiler (900oC). Pelet plastik rejek sebanyak 4,25% kapasitas produksi berpotensi dapat digunakan sebagai substitusi batubara bahan bakar boiler industri kertas dengan kecenderungan terjadinya slagging dan fouling dalam boiler rendah.Kata kunci : batubara, industri kertas, pelet, plastik, rejek, bahan bakar